Study of Spatial Orientation of Angular Momentum of z-Magnitude SDSS DR-13 Galaxies with Red Shift 0.50 to 0.53 - Yadav, Shiv Narayan; Sah, Santosh Kumar (Journal of Institute of Science and Technology, 2021)
The spatial orientations of 142,929 SDSS DR-13, z- magnitude galaxies having red shift 0.50 to 0.53 have been analyzed. The main goal of this work is to examine the orientation of the angular momentum of galaxies within the given redshift limit in the framework of three different scenarios 'Hierarchy model', 'Pancake model', and the 'Primordial vorticity model'. By using Godlowskian transformation the two-dimensional data were converted into three-dimensional data (polar and azimuthal angles). The expected isotropy distribution curves were obtained by removing the selection effects and performing a random simulation to generate 107 virtual galaxies by using Matlab 2015a. Three statistical tests of Chi-square, autocorrelation, and Fourier were used to compare the expected isotropic data with observed. The data classified into nine subsamples having each of one magnitude size. In general, the results supported the Hierarchy model. The model advocates random orientations of angular. However, a local anisotropy observed in few subsamples suggested a gravitational tidal interaction between neighboring galaxies, an early-merging process in which the angular momentum vector distorts the initial alignment of nearby galaxies.